Chemical-recognition-driven selectivity of SnO2-nanowire-based gas sensors. (October 2021) - Park, Hyoungwon; Kim, Jae-Hun; Vivod, Dustin; Kim, Sungil; Mirzaei, Ali; Zahn, Dirk; Park, Changkyoo; Kim, Sang Sub; Halik, Marcus
Highlights: Proposing a simple and an efficient method to modulate the selectivity of the gas sensor. Use of SAM molecules with different chemical moieties for tuning the selectivity of SnO2 nanowires-based gas sensors. Adsorbed SAM molecules acted as a passivation layer and lowered the base resistance and the operating temperatures. Gas sensing studies showed distinct selectivity behavior for each SAM molecules. Molecular dynamic simulation further supports the selective gas sensing mechanism. Graphical Abstract: ga1 Abstract: The sensing capabilities of semiconducting metal oxide (SMO)-based gas sensors, which are a promising type of sensors, were improved in the present study using a novel method that enhanced gas selectivity toward various gas molecules. A simple and effective post-modification with functional self-assembled monolayer (SAM) molecules enhanced the selective sensing properties. The chemical-affinity-driven interaction between SAM and gas molecules enabled selective gas sensing, and the small size of SnO2 nanowires (NWs; diameter = 50 nm) provided a large sensing area. Moreover, simple alteration of the chemical moiety in SAM molecules facilitated the tuning of SAM-induced selectivity over a broad range of collections. The binding of SAMs on the NWs was analyzed by infrared spectroscopy, thermogravimetric analysis, and X-ray photoelectron spectroscopy, with the selective gas sensing being investigated under various sensing conditions. The results from the molecular dynamics simulations supported the proposed selective sensing mechanism. The combination of passivation and selective gas sensing resulted in a simple method for the selective gas sensing of SnO2 NWs, and the concept could be generally expanded to other types of SMO-based sensing platforms.